Partial Substitution of Soyabean Meal with Breadfruit (Artocarpus altilis) Seed Meal in Broiler Starter Diets: Effects on Performance, Water Consumption and Carcass Characteristics - Nwokoro,; O., Smart; Obasuyi, Joseph O.I. (International Journal of Poultry Science, 2006)
The study was initiated to ascertain the effect of partial substitution of soyabean meal with breadfruit (Artocarpus altilis) meal in broiler starter chickens diets reared in a tropical environment. 300 broilers chicks were used for the study and they were divided into 15 replicate groups such that three replicates were allocated to a diet. Five broiler starter diets (3000 Kcal MEKg-1 and 24% CP) were formulated such that the Soya bean meal in the diet were replaced with breadfruit seed meal at 0, 10. 20, 30 and 40% levels. The birds were fed and watered ad libitum for the 4 weeks of the study. Results indicated that final live weights of birds, weight gain, feed and water intakes, daily nitrogen retention, packed cell volume and back wholesale carcass cuts of the broilers indicated significant (P< 0.05) differences. It also showed that birds on control diet (diet 1) recorded significantly (P< 0.05) higher body weight, weight gain, feed intake than those of other diets (10, 20, 30 and, 40 % breadfruit seed meal based) which were not different from each other. There were consistent decrease in feed and water consumption with increasing breadfruit meal level of dietary inclusion. Results for the nitrogen retention revealed that the best values were recorded in diets 3 and 4 followed by diet 5, while the least were obtained in diets 1 and 2. Results for the blood metabolites indicated that only PCV and globulin showed significant differences, where only diet 5 (for PCV) were different from all other diets. Other parameters measured were not consistent. The value for the carcass back cut indicated a decreasing back cut between diet 1 and 5 with the exception of diet 3. Treatments had no effect on mortality.